CALCULATION OF THE ISOTROPIC EFFICIENCY OF A GAS TURBINE USING THE OPERATIONAL DATA OF THE FIRST UNIT OF THE AL-KHOUMS GAS POWER PLANT - Allafi, Musa; Shalawh, Abduelrhman; Ganaw, Mustafa (Conference On Engineering Science and Technology, 2021)
The isotropic efficiency of a gas turbine is very important for using thermal energy and converting it into kinetic energy to rotate the turbine, and because of the irreversibility in the thermal cycle of the compressor and turbine, the ideal cycle of the gas turbine is different from the real one, which results in a deviation from the ideal values of pressure and temperature, causing the real efficiency of the gas turbine to be lower than the ideal. In this paper, the operational data of the gas turbines (first unit in Al-khoums power plant) were used to calculate the isotropic efficiency of the turbine, where the data were chosen to include most months of the year. The results showed that the isotropic efficiency of the turbine is about 90%, and it was found that the value of the heat energy lost from turbine due to low efficiency ranges from 12% to 15% of the theoretical temperature leaving the turbine. And it was found that the real temperature comes out of the turbine and is thrown into the air up to about 489 degrees Celsius in summer, while it drops in winter to about 367 degrees Celsius